The association between dietary inflammation index and depression - Luo, Ling; Hu, Jie; Huang, Ruixian; Kong, Danli; Hu, Wei; Ding, Yuanlin; Yu, Haibing (Frontiers in Psychiatry, 2023)
Objective: We aimed to evaluate whether depression is associated with increased risk of dietary inflammatory index (DII) or energy-adjusted DII (E-DII) and whether the association is partly explained by insulin resistance (IR). Methods Base on the National Health and Nutrition Examination Survey (NHANES) 2005 - 2018. Univariate analyses of continuous and categorical variables were performed using t-test, ANOVA, and χ2 test, respectively. Logistic regression was used to analyze the relationship between DII or E-DII and depression in three different models. Mediation analysis was used to assess the potential mediation effects of homeostatic model assessment-IR (HOMA-IR). Results A total of 70,190 participants were included, and the DII score was higher in the depressed group. DII score was related to all participant characteristics except age (P 0.05). After being included in covariates (Model 3), participants in the highest quartile of DII score have increased odds of depression (OR: 1.82, 95% CI: 1.28 - 2.58) compared with those in the first quartile of DII score. And, a significant dose-response relationship was found (P-trend 0.05). No interaction between DII and HOMA-IR was observed in terms of the risk of depression, and HOMA-IR did not find to play a mediating role in the association between DII and depression. Similar results were obtained for the association between E-DII and depression. Conclusions Our results suggest that a higher pro-inflammatory diet increases the risk of depression in U.S. adults, while there was no evidence of a multiplicative effect of DII or E-DII and HOMA-IR on disease risk, nor of a mediating effect of HOMA-IR.